A tale of two rural cities: Dynamics of community capitals during a North Dakota oil boom. Issue 3 (27th May 2018) - Fernando, Felix N.; Goreham, Gary A.
Abstract: The Community Capitals Framework was used in this study to understand, compare, and contrast how an oil boom is changing the nature, character, and context of two rural cities, "Minor" and "Major." Minor and Major are the county seats of two adjacent counties located in the heart of the North Dakota Bakken region. This study examines the changes and impacts caused by the oil boom through the lens of community capitals. The study investigates the relationships, dependencies, and interactions among the capitals and the challenges that need to be addressed. Findings of this study show that, within the context of rapid energy development, the specific interactions among the capitals are multidimensional and the overall process represents a dual effect. The findings highlight the importance of investing in social capital, addressing the changes in cultural capital and the need to mobilize local political capital to address the community-level boom impacts.